TRPV1 channel in human eosinophils: functional expression and inflammatory modulation - Weihrauch, Tobias; Gray, Natalie; Wiebe, Daniela; Schmelz, Martin; Limberg, Maren M.; Raap, Ulrike (International journal of molecular sciences, 2024)
The transient receptor potential vanilloid 1 (TRPV1) is a non-selective cation channel expressed on sensory neurons and immune cells. We hypothesize that TRPV1 plays a role in human eosinophil function and is modulated by inflammatory conditions. TRPV1 expression on human eosinophils was examined by qPCR, flow cytometry, and immunohistochemistry, respectively. TRPV1 functionality was analyzed by investigating calcium flux, apoptosis, modulation by cytokines and acidic pH, and CD69 externalization using flow cytometry. Activation of TRPV1 induced calcium influx and prolonged survival. Although eosinophils were not directly activated by TRPV1 agonists, activation by IL-3 or GM-CSF was mainly restricted to TRPV1-positive eosinophils. TRPV1 surface content was increased by acidic pH, IL-3, IL-31, IL-33, TSLP, TNF-α, BDNF, and NGF-β. Interestingly, TRPV1 was also expressed by eosinophils located in proximity to peripheral nerves in atopic dermatitis (AD) skin. In conclusion, eosinophils express functional TRPV1 channels which are increased by extracellular acidification and AD-related cytokines. Since eosinophils also express TRPV1 in AD skin, our results indicate an important role of TRPV1 for neuroimmune interaction mechanisms in itchy, inflammatory skin diseases, like AD.